Answer :

Given: sec θ + tan θ = x ……………(i)

To find: sec θ – tan θ

We know that 1 + tan2 θ = sec2 θ

1 = sec2 θ – tan2 θ

Now, a2 – b2 = (a – b) (a + b)

1 = sec2 θ – tan2 θ = (sec θ – tan θ) (sec θ + tan θ)

From (i), we have

1 = (sec θ – tan θ) x

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Trigonometric IdentitiesTrigonometric IdentitiesTrigonometric Identities39 mins
Trigonometric Identities-IITrigonometric Identities-IITrigonometric Identities-II43 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses